DEKONSTRUKSI FEMINITAS DALAM GERAKAN TERORIS DI DUNIA ISLAM - Nurhayati, Aniek (Jurnal Review Politik, 2015)
Nowadays, the world has been stunned by the acts of terror committed by women. This is done by Islamic terrorist groups, which have very conservative views on women. It has been frequently reported that these groups have threatened women from getting education and the "friendly" public domain. However, the terrorist leaders see that recruitment of women terroristsis an important matter. It is an interesting issue to analyze. Based on library research this article attempts to look at this reality as a part of the postmodern phenomenon, which seeks to deconstruct the already established discourse. The article examines the terror movement, relativity, flexi-bility, and deconstruction of the conservative texts about women carried out by the Islamic terrorist groups.